Mumford on aesthetic–moral interaction in sport. Issue 1 (2nd January 2017) - Holt, Jason
Abstract: Stephen Mumford argues that aesthetic and moral values in sport are interdependent, focusing on cases where immorality taints beautiful performance. This interdependence thesis is insightful but, I argue, in need of refinement, as its normative implications are unclear and perhaps implausible (e.g. the Nazi aesthetics problem). I also challenge Mumford's perspective on the infamous Dynamo Kiev death match. Whereas Mumford claims that the match's morally oppressive circumstances detract from it so that 'it was not something knowingly we should have admired aesthetically', I argue that, on the contrary, and in light of what Mumford says about other cases, such circumstances actually enhance the game's aesthetics such that it would be wrong not to appreciate it aesthetically.